Cross-cultural adaptation and psychometric properties of the Indonesian version for quality of life among breast cancer patients - Solikhah, Solikhah; Perwitasari, Dyah Aryani; Rejeki, Dwi Sarwani Sri (Frontiers in Public Health, 2023)
Background: Breast cancer is one of the most important health problems worldwide. Quality of life (QoL) is an important indicator to evaluate symptoms in cancer patients, including those with breast cancer. Culturally suitable, valid, reliable, and appropriate instruments to measure the QoL of breast cancer patients are needed, which is still rare in Indonesia. This study aimed to translate the EORTC QLQ-BR45 instrument into Indonesian and evaluate its psychometrics. Methods: A cross-sectional study was performed on 635 patients conveniently selected from the oncology department in referral hospital. The first phase of this study involved translation of the existing EORTC QLQ-BR45 into Indonesian, and in the second phase, we evaluated its psychometric properties. Construct validity was evaluated using confirmatory factor analysis (CFA). Criterion validity was examined according to the association between disease stage and Karnofsky Performance Scale (KPS). Results: A total of 635 (99.00%) completed the EORTC QLQ-BR45 successfully. The instrument indicated good readability and high content validity. All Cronbach's alpha coefficients were satisfactory (overall value, 0.87). For construct validity, patients with KPS ≥80% did better than those with KPS ≤70%, as did two multi-item scales in functional scales (body image and breast satisfaction) and five multi-item scales in symptom scales (systemic therapy side effects, endocrine therapy, and arm, breast, and endocrine sexual symptoms). Body image score of late-stage patients was significantly higher. CFA indicated that the nine-factor structure of the Indonesian EORTC QLQ-BR45 was a good fit for the data. Conclusion: The Indonesian EORTC QLQ-BR45 questionnaire is reliable and valid with good psychometric properties, thus can be used for breast cancer patients in Indonesia.